2017
DOI: 10.3233/jad-170093
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Ameliorates Neuroinflammation, Neurodegeneration, and Memory Deficits in p25 Transgenic Mouse Model that Bears Hallmarks of Alzheimer’s Disease

Abstract: Several studies have indicated that neuroinflammation is indeed associated with neurodegenerative disease pathology. However, failures of recent clinical trials of anti-inflammatory agents in neurodegenerative disorders have emphasized the need to better understand the complexity of the neuroinflammatory process in order to unravel its link with neurodegeneration. Deregulation of Cyclin-dependent kinase 5 (Cdk5) activity by production of its hyperactivator p25 is involved in the formation of tau and amyloid pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 58 publications
2
37
0
Order By: Relevance
“…Sundaram and colleagues (2017) [111] studied the effects of early intervention with a potent natural anti-inflammatory agent, curcumin, on Cdk5 dependent p25-mediated neuroinflammation and the progression of neurodegeneration in p25 transgenic mice. They found that curcumin effectively counteracted the p25-mediated glial activation and pro-inflammatory chemokines/cytokines production in p25Tg mice.…”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Sundaram and colleagues (2017) [111] studied the effects of early intervention with a potent natural anti-inflammatory agent, curcumin, on Cdk5 dependent p25-mediated neuroinflammation and the progression of neurodegeneration in p25 transgenic mice. They found that curcumin effectively counteracted the p25-mediated glial activation and pro-inflammatory chemokines/cytokines production in p25Tg mice.…”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…In line with this, their results demonstrated that early intervention of inflammation could reduce the progression of AD-like pathological outcomes. Moreover, their data provide a rationale for the potential use of curcuminoids in the treatment of inflammation associated neurodegenerative diseases [111]. …”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…Curcumin improved AD-related cognitive deficits via upregulating brain-derived neurotrophic factor (BDNF)-ERK signaling in the hippocampus of rats (L. Zhang et al, 2015). The neuro-inflammation reduced the progression of p25-induced tau/ amyloid pathology and in turn attenuated the p25-induced cognitive deficiency (Sundaram et al, 2017). Curcumin ameliorated AD in transgenic mice by decreasing caveolin-1, inhibiting the abnormal phosphorylation of Tau and inactivating GSK-3β (Sun, Zhang, Wang, Teng, & Li, 2017).…”
Section: Additionally Curcumin Prevented Oligomerization Of Aβ By Bimentioning
confidence: 99%
“…10) Therefore, FA is expected to act relatively upstream of the pathophysiologic mechanism of AD. On the other hand, many studies have reported that Cur not only inhibits Aβ production 28,25) but also inhibits tau phosphorylation 32,39,40) and its aggregation. 41,42) Therefore, Cur is also expected to act downstream of the pathophysiologic mechanism of AD.…”
Section: Discussionmentioning
confidence: 99%
“…35) Cur also inhibits Aβ aggregation 8,36) and promotes Aβ clearance via up-regulation of degrading enzymes 37) and induction of autophagy. 38) In addition, Cur also reduces hyperphosphorylated tau via down-regulation 39) and inhibition 32) of glycogen synthase kinase 3β (GSK3β) and inhibition of cyclin-dependent kinase 5, 40) inhibits tau aggregation, 41,42) exhibits some kinds of neuroprotective effects, [43][44][45] and promotes neurogenesis via histone acetylase inhibition 46) and BDNF expression. 47) As a result, the incidence of AD in the United States is higher compared to India, where Cur is consumed on a daily basis.…”
Section: Introductionmentioning
confidence: 99%